Menggali Pemikiran Friedrich Silaban: Arsitektur, Spiritualitas, dan Ketahanan di Tengah Krisis Melalui Pendekatan Teori Pierre Bourdieu "Habitus" - Syifa Mutia Ramadhani; Rumaisya Rumaisya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Friedrich Silaban is one of Indonesia's prominent architects, renowned for his ability to integrate cultural and spiritual values into each of his works. This article explores Silaban's thoughts and design philosophy, which reflect the close relationship between architecture and spirituality. Through an approach that emphasizes aesthetics, functionality, and social context, Silaban successfully creates spaces that are not only beautiful but also meaningful, reflecting the identity of Indonesian society. In facing the challenges of the times, including political and social crises, Silaban's resilience and creativity serve as a testament to how architecture can adapt and endure. This article also discusses Silaban's legacy, which continues to inspire generations of contemporary architects, as well as the importance of understanding architecture as a medium for creating spaces that embody spiritual and cultural values. Thus, Friedrich Silaban's thoughts not only make a significant contribution to the world of architecture but also invite us to reconsider the meaning of space in our lives.